Penerapan Metode Pembelajaran Team Games Tournament Pada Pelajaran IPAS Materi Persebaran Flora Dan Fauna Di Indonesia Untuk Meningkatkan Hasil Belajar Dan Keaktifan Peserta Didik Kelas V SD Negeri Cikaret 01 Kecamatan Cibinong - Rahman Andrean Kurniadya; Fauzi Fadliansyah (Desanta Publisher, 2024)
The aim of this learning improvement research is to improve learning outcomes and student activity in the science and science learning process for class V of SD Negeri Cikaret 01, Bogor Regency through the application of the Team Games Tournament learning method. This research is classroom action research carried out in two cycles and carried out at SD Negeri Cikaret 01, Bogor Regency. The subjects of the research were teachers and students of class V. Data was collected and analyzed using qualitative and quantitative data analysis techniques. The results of this research show that through the application of the Cooperative learning method (Team Games Tournament) the quality of science and science learning can be improved. Learning results show that the percentage in cycle I was 58.62% in the sufficient category, increasing in cycle II to 89.65% in the good category. On the other hand, the percentage of student activity in cycle I was 55.17% in the sufficient category, in cycle II the percentage was 86.20% in the good category. Based on these results, it can be concluded that the Team Games Tournament learning method can improve the quality of class V science and science learning at SD Negeri Cikaret 01, Bogor Regency.